2017
DOI: 10.1177/0306307017723313
|View full text |Cite
|
Sign up to set email alerts
|

Managerial support

Abstract: This study investigates how Australian employees perceive managerial support and the influence of union membership on their perception of managerial support using data from 4124 employed persons in Australia across a range of industry sectors. The results indicate that employee perceptions of the work environment (control over working hours, job security, pay equity and safety) influence their perceptions of managerial support, regardless of union membership. The findings imply that managers have a critical ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(59 reference statements)
0
2
0
2
Order By: Relevance
“…The need for mutual support between leaders/managers and employees has recently attracted the attention of management scholars (Kurtessis et al, 2017; Van Buren, Greenwood, and Sheehan, 2011), and one of the reasons is organizations' shift from an employee focus to a strategic focus (Van Buren, Greenwood, and Sheehan, 2011). The relationship between employers and their employees is one of mutual obligation (Boxall, and Macky, 2009;Johns, 2006;Travaglione et al, 2017). Building a relationship of mutual respect where employees perceive that their needs are considered and are acted upon appropriately lies at the heart of managerial support (Travaglione et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for mutual support between leaders/managers and employees has recently attracted the attention of management scholars (Kurtessis et al, 2017; Van Buren, Greenwood, and Sheehan, 2011), and one of the reasons is organizations' shift from an employee focus to a strategic focus (Van Buren, Greenwood, and Sheehan, 2011). The relationship between employers and their employees is one of mutual obligation (Boxall, and Macky, 2009;Johns, 2006;Travaglione et al, 2017). Building a relationship of mutual respect where employees perceive that their needs are considered and are acted upon appropriately lies at the heart of managerial support (Travaglione et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between employers and their employees is one of mutual obligation (Boxall, and Macky, 2009;Johns, 2006;Travaglione et al, 2017). Building a relationship of mutual respect where employees perceive that their needs are considered and are acted upon appropriately lies at the heart of managerial support (Travaglione et al, 2017). Such support can also facilitate the communication and implementation of strategic decisions (Dasgupta, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Potrzeba wzajemnego wsparcia między liderami/menedżerami a pracownikami przyciągnęła ostatnio uwagę uczonych zajmujących się zarządzaniem (Kurtessis i in., 2017;Van Buren i in., 2011), a jednym z powodów jest przesunięcie organizacji z koncentracji na pracownikach na koncentrację strategiczną (Van Buren i in., 2011). Relacja między pracodawcami a ich pracownikami jest relacją wzajemnego zobowiązania (Boxall i Macky, 2009;Johns, 2006;Travaglione i in., 2017). Budowanie relacji opartej na wzajemnym szacunku, w której pracownicy dostrzegają, że ich potrzeby są brane pod uwagę i odpowiednio realizowane, leży u podstaw wsparcia menedżerskiego (Travaglione i in., 2017).…”
Section: Lider W Przestrzeni Społeczno-ekonomicznejunclassified
“…Relacja między pracodawcami a ich pracownikami jest relacją wzajemnego zobowiązania (Boxall i Macky, 2009;Johns, 2006;Travaglione i in., 2017). Budowanie relacji opartej na wzajemnym szacunku, w której pracownicy dostrzegają, że ich potrzeby są brane pod uwagę i odpowiednio realizowane, leży u podstaw wsparcia menedżerskiego (Travaglione i in., 2017). Takie wsparcie może również ułatwiać komunikację i wdrażanie decyzji strategicznych (Dasgupta, 2015).…”
Section: Lider W Przestrzeni Społeczno-ekonomicznejunclassified
“…With reference to commonly implemented organization practices, most research studies conducted prior to the pandemic suggest that the appropriate workplace practices can enhance employees' physical, psychological, and social well-being for optimal job performance [21] [22] [23]. Specifically, it was found that providing autonomy and flexibility, placing trust on them, creating a safe workplace atmosphere, and communication clarity lead to positive accomplishments in the workplace [21] [23] [24]. Further, appropriate interventions for proper use of technologies for remote work led to get work done effectively [17].…”
Section: Organization-initiated Support Interventionsmentioning
confidence: 99%